Ignimbrite Analyses of Batur Caldera, Bali, based on 14C Dating - Igan S. Sutawidjaja (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20094The Batur Caldera, in the northeastern part of Bali Island, is an elliptical collapse structure 13.8 by 10 km in size and another circular composite collapse structure with a diameter of 7.5 km in its centre. Two stages of the collapse were interrupted by silicic andesite lavas and domes. The first collapse was initiated by the eruption of about 84 km3 of the dacitic "Ubud Ignimbrite", about 29,300 years B.P., which caused a steep-walled depression about 1 km deep. The second ignimbrite was erupted from a large crater about the present lake, and it  produced about 19 km3 of a similar voluminous dacitic ignimbrite, called the "Gunungkawi Ignimbrite" about 20,150 years B.P. This second eruption trig- gered a second collapse, which created the central circular caldera, and formed a basin structure. Both the Ubud and Gunungkawi Ignimbrites consist of a similar dacitic composition, white to red (the most abundant nearly 90 %) and dark grey to black dacitic pumice clasts. The large clasts, up to 20 cm in diameter, are in the non-welded ignimbrite, particularly in the upper part of the Gunungkawi Ignimbrite. The intracaldera ignimbrite, called the "Batur Ignimbrite" about 5 km3  in volume is a densely welded ignimbrite and generally shows typical welded features. The ignimbrite comprises at least five different flow units, separated by thin (15 - 40 cm) welded pumiceous airfall deposits, with flattened pumice clasts. Another large eruption occurred about 5,500 years B.P., producing around 0.09 km3  andesitic ignimbrite. This was initiated by phreatomagmatic eruptions, indicated by thick phreatomagmatic and surge deposits, underlying the ignimbrite. The caldera and its vicinity are partly filled, and variably mantled by later eruptive products of dacitic and andesitic phreatomagmatic and airfall deposits.